The berenstain bears and the baby chipmunk eaudiobook - Berenstain, Jan (I Can Read, Level 1: Berenstain Bears., 2012)
The Bear family adopts a curious baby chipmunk. Brown Eyes explores Papa's desk, Mama's sewing basket, and Papa's pant leg –– all the way up to the knee!